Pengaruh Efikasi Diri Terhadap Hasil Belajar Mahasiswa Pada Matakuliah Metode Numerik - sri rezeki; Rahmawati Yuliyani; Bayu Jaya Tama (Universitas Majalengka, 2023)
Self-efficacy is an assessment of a person's belief in the ability or potential that is possessed within him. This self-efficacy is very important for students, because this self-efficacy is a student's self-confidence in their potential, then how do they overcome an action against a given task so that they can achieve the goals they want, and this can also affect their learning outcomes .This study aims to see the effect of self-efficacy on the learning outcomes of students taking the Numerical Method course. The sample of this study were students of the Unindra Informatics Engineering Study Program who took the Numerical Method course. The instruments in this study were self-efficacy questionnaires and post-tests. Data analysis was carried out quantitatively. Data analysis was performed on the post-test data by using a linear regression analysis test. Meanwhile, student self-efficacy is in the form of distributing questionnaires which are then processed quantitatively. The results showed that there was an effect of self-efficacy on student learning outcomes in the Numerical Method course. The regression model test shows that the F test is 109.541 with a significance level of 0.00 <0.05. This shows that there is a significant influence between student self-efficacy on learning outcomes. The value of the correlation coefficient (R) is 0.826, this shows that there is a relationship between self-efficacy and student learning outcomes in the high category. Based on the results of the determinant coefficient (R2) it is obtained that 68% of student learning outcomes are influenced by self-efficacy variables, while 32% are influenced by other factors.Â